2019
DOI: 10.1039/c9dt02570g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(ii) complexes with thiosemicarbazones derived from pyrene as topoisomerase IB inhibitors

Abstract: New palladium complexes exhibit potent antiproliferative activity against A2780 and cisplatin-resistant A2780C is human ovarian cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…Thiosemicarbazones (TSC) have been studied in the last 70 years with regard to their use as versatile ligands in coordination chemistry [1–17] with applications in transition metal catalysis, [1,4–6] and as materials for biomedical imaging and treatment [5–17] . TSCs of heterocycles, especially pyridine, form a vast group within the class of TSC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiosemicarbazones (TSC) have been studied in the last 70 years with regard to their use as versatile ligands in coordination chemistry [1–17] with applications in transition metal catalysis, [1,4–6] and as materials for biomedical imaging and treatment [5–17] . TSCs of heterocycles, especially pyridine, form a vast group within the class of TSC.…”
Section: Introductionmentioning
confidence: 99%
“…TSCs of heterocycles, especially pyridine, form a vast group within the class of TSC. They can act as tridentate N^N^Sx chelate ligands forming stable complexes with many metals [1–3] and many studies have shown their cytotoxic behaviour with and without a coordinated metal ion [14–20] …”
Section: Introductionmentioning
confidence: 99%
“…Unlike copper, there is no evidence regarding any biological functions of palladium [14]. DNA-binding studies of palladium-based complexes have been investigated [15][16][17][18][19] due to their structural similarities with Pt(II) compounds. Indeed, a square-planar geometry is favored for both metal ions; however, the ligand-exchange kinetics is faster for palladium compounds, generating more reactive compounds that may interact with pharmacological targets in distinct ways [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a number of copper(II) and palladium(II) compounds have been investigated as potential DNA binders and/or cleavers [17,18,[23][24][25]. In a previous study, we investigated the DNA-interacting and cytotoxic properties of a dinuclear [Cu(L)Cl 2 ] 2 complex, where L is a Schiff base ligand, namely (E)-phenyl-N-((pyridin-2-yl)methylene)methanamine [26].…”
Section: Introductionmentioning
confidence: 99%
“…Among organic reagents, thiosemicarbazones have a vital role due to the ability of formation of bonds with enzymes in biological systems. The donor atoms of nitrogen and sulphur of thiosemicarbazones forms a chelating bonds with the wide range of metal ions [1][2][3][4] . In recent years, so many authors were reported regarding the synthesis and characterization studies of thiosemicarbazones and their metal complexes.…”
Section: Introductionmentioning
confidence: 99%